STORY TELLING METHOD TO IMPROVE EARLY CHILDHOOD VOCABULARY - Lara Juita; Putri, Melisa Rahma; Angel Rosi Ameliaa; Windi Dwi Andika; Najlatul Fatiyah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Vocabulary mastery is a crucial aspect of early childhood language development, as it plays a significant role in children's ability to express ideas, convey emotions, and understand their surroundings. This study aims to examine the effectiveness of the storytelling method in enhancing vocabulary acquisition in early childhood by conducting a literature review of eight scientific journals published between 2020 and 2025. A descriptive qualitative approach was employed for the literature review. The analysis reveals that storytelling whether carried out conventionally or supported by various media such as flashcards, hand puppets, interactive storybooks, pictures, and digital tools effectively enriches children’s vocabulary. The use of supplementary media enhances the appeal of the stories and increases children’s engagement in the learning process. These findings align with constructivist theory, which emphasizes the importance of active and concrete learning experiences. Therefore, storytelling should be considered a primary strategy in developing early childhood language skills.